Minimization of heat gains in buildings: The case of domestic buildings in Cape Coast Metropolis – Ghana - Samuel Kwame Ansah (International Journal of Development and Sustainability, 2014)
This research aims at ascertaining appropriate construction designs and techniques that could be adopted to minimize excessive heat gains in buildings. Random sampling technique was used for selecting hundred (100) domestic buildings in each of the three densely populated suburbs considered within the Cape Coast Metropolis in Ghana. In total, three hundred (300) buildings were used as a sample for this study. Structured interview and observation were used as the main research methods to obtain the necessary data for the study objectives. The results show that appropriate construction designed methods and techniques were not adopted for the construction of almost all the buildings investigated. It was also realized that majority of the occupants (96%) used electric fans, and air conditioners to reduce the amount of heat gains in their rooms. The study suggested that, shading techniques such as screens to walls, fixed sun breakers and attached canopies must be encouraged in the design and construction of buildings. The study also suggested that all buildings, yet to be constructed, should be positioned with their longest walls facings north and south in order to reduce intense morning and evening sun entering into the building with more window openings accommodated in both sides of the longest walls to allow for cross ventilation.